Environmental Risk Factors associated Helicobacter pylori Infection Among Dyspeptic Patients (Journal of Humanitarian and Applied Sciences, 2023)
Helicobacter pylori (H. pylori) infections occur earlier in life with high frequency in developing countries. It has been reported that the source of drinking water as a potential route of transmission. In Libya, there is no data available regarding the prevalence of H. pylori infection in dyspeptic children and adults, and its associated risk factors in rural regions. Objectives: To establish the current prevalence of H. pylori infection among dyspeptic Children & Adults attending Alkomes Teaching Hospital & its associated risk factors. Materials and Methods: A Blood sample of (350) dyspeptic Children and Adults patients (mean age29 years), using ELISA method to detect anti-H. pylori IgG, and questionnaire covering Socio demographic variables were completed by interview. Results:- The overall, sero prevalence of H. pylori was (41%). However, H. pylori was (23%), (77%) in children and Adults respectively. The gastric pathogen was in male (56%) than the female (44%).There was a gradual increase with age. The higher positive infected H. pylori in subjects who are using private untreated well-water drinking than those the commercial water supply. Conclusions: In Al- Komes region, the prevalence of the gastric H. pylori is high in the group of dyspeptic participants of the population study, which might be related to the socioeconomic status, and living conditions, as major risk factors for H. pylori infection. Our data indicate that the source of drinking water is an important mechanism for the transmission of H. pylori in a rural regions. However, larger studies in other regions of Libya should be conducted to confirm the study finding, using molecular typing techniques to help trace the route of transmission in future.
Keywords: Helicobacter pylori; Prevalence; Serology; libya; Dyspeptic